Effects of Endurance Training and Chlorogenic Acid on Oxidative and Nitrosative Stress Markers in Prediabetic Male Mice - Sahar Ghasemi Pour; Sayyed M. Marandi (International Journal of Preventive Medicine)
Background: Many studies have investigated the effects of exercise and chlorogenic acid in controlling and improving diabetes and reducing inflammation. This study aimed to investigate the effects of endurance exercise and chlorogenic acid on oxidative and nitrosative stress indicators in skeletal muscle tissue of male C57BL/6 mice. Methods: A total of 35 mice were randomly divided into two groups: a high-fat diet group to induce pre-diabetes and a normal diet group. After inducing pre-diabetes, mice in the high-fat diet group were further divided into control, chlorogenic acid, endurance training, and endurance training + chlorogenic acid groups (n = 7). The exercise protocol was performed incrementally (speed 15–23 m/min) for 10 weeks (three sessions per week for 45 min) on a treadmill. Chlorogenic acid was administered at a rate of 110 mg/kg of body weight three times a week via gavage. Next, 24 hours after the last intervention, tissue samples were taken from the quadriceps femoris muscles and analyzed using the enzyme-linked immunosorbent assay (ELISA) method. Data were analyzed using one-way analysis of variance and Dunnett’s post-hoc test at a significance level of P < 0.05. Results: Endurance training significantly decreased glutathione (P = 0.01) and glutathione peroxidase (P = 0.026). Chlorogenic acid consumption also significantly decreased glutathione peroxidase (P = 0.007) and significantly increased the total antioxidant capacity (P = 0.011). Conclusion: Endurance training and chlorogenic acid supplementation may be used as therapeutic strategies to improve antioxidant capacity and prevent or reduce diabetes-related complications.